Assessment of health status and cardiovascular risk factors in a Roma population sample from South Bulgaria - Delcheva, Ginka; Stankova, Teodora; Stefanova, Katya; Bivolarska, Anelia (Central European Journal of Public Health, 2023)
OBJECTIVES: Roma population is one of the major ethnic groups in the Central and Eastern Europe, having high rates of chronic diseases and associated risk factors related to their poor social conditions, unhealthy lifestyle and low educational level. The purpose of our study was to assess the health status of Roma from South Bulgaria by means of blood indicators and determine the prevalence of some cardiovascular (CV) risk factors in the Roma population sample. METHODS: The study group consisted of 60 Roma (23 men and 37 women), mean age 53.7 ± 15.9 years, and the control group consisted of 68 non-Roma from the majority population (29 men and 38 women), mean age 45.8 ± 12.2 years. The data were collected via questionnaire, anthropometric measures, and venous blood samples analyses after an overnight fasting. RESULTS: The Roma population subjects were slightly but significantly older compared to the non-Roma group and both study groups included more women. The fasting glucose, body mass index (BMI), triglycerides (TG), total cholesterol (TC), and LDL-cholesterol (LDL-C) levels were significantly higher, and HDL-cholesterol (HDL-C) levels were significantly lower in Roma compared to the control non-Roma group. The values of cardiovascular risk markers such as TC/HDL-C and TG/HDL-C ratios, atherogenic index of plasma (AIP) and lipoprotein combine index (LCI) were significantly higher in Roma compared to non-Roma subjects. The prevalence of obesity in Roma was 35%, diabetes mellitus was recorded in 16.7% of the entire Roma sample, and hyperglycaemia in non-diabetics was recorded in 32%. Hypercholesterolaemia was found in 90% and hypertriglyceridaemia was found in 88.3%. The prevalence of cardiovascular diseases (CVD) was high and was encountered in 71.7% of the Roma participants and most of the subjects (96.7%) reported family history of CVD. The studied population showed high smoking rates with 33.3% active smokers. CONCLUSIONS: Our study confirmed high prevalence of CV risk factors among Roma population, such as abnormal lipid profile parameters, obesity and heavy smoking and very high cardiovascular morbidity rate. Therefore, adequate measures and healthcare programmes aiming at the early identification, treatment and prevention of CVD risks among Roma are necessary.
Keywords: dospělí; Bulharsko; Female; Heart Disease Risk Factors; Adult; ženské pohlaví; triglyceridy; Obesity; Triglycerides; Health Status; lidé; zdravotní stav; rizikové faktory kardiovaskulárních chorob; Risk Factors; obezita; Male; Cardiovascular Diseases; Aged; Bulgaria; Cholesterol, HDL; HDL-cholesterol; rizikové faktory; kardiovaskulární nemoci; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Humans